Fetal/neonatal alloimmune thrombocytopenia due to anti‐CD36 antibodies: antibody evaluations by CD36‐transfected cell lines. Issue 1 (13th October 2017) - Lin, Marie; Xu, Xiuzhang; Lee, Hui‐Lin; Liang, Der‐Cheng; Santoso, Sentot
Abstract : BACKGROUND: Isoantibodies against CD36 (platelet glycoprotein 4), developed in Type I CD36‐deficient mothers are frequently reported as the cause of fetal/neonatal alloimmune thrombocytopenia in the Asian population. Therefore, further detailed characterization of anti‐CD36–mediated fetal/neonatal alloimmune thrombocytopenia is warranted. Here, we report the characterization of a patient with fetal/neonatal alloimmune thrombocytopenia in a Taiwanese family caused by anti‐CD36 isoantibodies using a novel antigen‐capture method. STUDY DESIGN AND METHODS: Platelets and monocytes were analyzed for CD36 expression by flow cytometry. Sequencing analysis of the CD36 gene was performed to identify the mutation underlying the CD36 deficiency. Stable transfected human embryonic kidney HEK293 cells expressing recombinant CD36 were established. These cells were used for the characterization of anti‐CD36 isoantibodies by flow cytometry, immunoprecipitation, and antigen‐capture assay. RESULTS: Flow cytometry analysis revealed a total absence of CD36 on both platelets and monocytes of the mother (Type I CD36‐deficient) caused by heterozygous deletions of the CD36 gene (332_333delCA and c.1254 + 6_1254 + 11delTATTTG). Analysis of maternal serum with CD36‐transfected HEK293 cells by flow cytometry, immunoprecipitation, and antigen‐capture assay demonstrated the presence of anti‐CD36 isoantibodies in maternal serum. Interestingly, this antibody could not be detected by the monoclonal antibody immobilization of platelet antigens assay when anti‐CD36 monoclonal antibody (clone FA6‐152) was used as the capture antibody. CONCLUSION: This case reemphasizes the role of anti‐CD36 isoantibodies on the pathomechanism of fetal/neonatal alloimmune thrombocytopenia. The fact that the monoclonal antibody immobilization of platelet antigens assay does not seem to be reliable for the identification of all anti‐CD36 antibodies indicates that screening of anti‐CD36 isoantibodies by a monoclonal antibody‐independent method, as presented here, should be considered.